Quantifying signal-to-noise ratio of mismatch negativity in humans. - Anthony T. Cacace; Dennis J. McFarland (Neuroscience letters, 2003)
Mismatch negativity (MMN) is thought to represent a neurophysiological index of auditory information processing that is independent of attention. Because this measure does not require an overt behavioral response, MMN has potential to evaluate higher order perceptual abilities in infants, young children and difficult-to-test populations, thereby extending results obtained from more basic physiologic and electroacoustic measures (auditory brainstem responses, ABRs; otoacoustic emissions, OAEs). Whereas the basic tenet of MMN is appealing, several issues-of-contention remain to be solved before this event related potential (ERP) can be applicable for routine clinical use. These issues include the consistent identification of MMN within individuals (vs. groups), its stability over time, and its reportedly poor signal-to-noise ratio (SNR). Herein, we focus on the issue of SNR, by comparing and contrasting SNR of MMN with other long latency auditory ERPs.
Keywords: auditory brainstem responses; event related potential; mismatch negativity; otoacoustic emissions; signal-to-noise ratio